Pendekteksian Kecurangan Laporan Keuangan Menggunakan Beneish M-Score Model Pada Perusahaan Perbankan Periode 2014-2018 - Warseno Warseno; Sri Sulistyaningsih; Ageng Setiani Rafika (IJAcc, 2023)
This study aims to find out which banking companies belong to manipulator companies and non manipulator companies, know how many percent of banking companies belong to manipulator companies and whether there is an increase or decrease in the number of banking companies classified as manipulators or non-manipulators from 2014 to 2018 The object of this research is all banking companies listing on the Indonesia Stock Exchange that publish audited financial statements for the 2014 to 2018 financial year, total 45 companies. The sampling technique uses a non-probability method - purposive sampling which results in a sample of 28 banking companies. The type of data used in this study is quantitative secondary data, namely in the form of financial statements from 2014 to 2018. The data sources are obtained from the official website, www.idx.co.id and www.sahamok.com Data collection methods use the library research method and The data analysis technique used is quantitative descriptive analysis using the Beneish Ratio Index. The variables in this study are Days' Sales In Receivables Index (DSRI), Gross Margin Index (GMI), Asset Quality Index (AQI), Sales Growth Index (SGI), Depreciation Index (DEPI), Sales, General Administrative Expense Index (SGAI). ), Leverage Index (LVGI) and Total Accruals To Total Assets Index (TATA). The conclusion of this study is that there are 9 banking companies or 32% belonging to manipulator companies and 19, 68% banking companies that are classified as non-manipulators and in the 2014 to 2018 period experienced a fluctuating level of financial statement fraud, namely in 2014 to 2017 manipulator companies experienced a decline however, 2018 has increased. Likewise with the opposite in non-manipulator companies.